2004
DOI: 10.1007/s00466-004-0623-8
|View full text |Cite
|
Sign up to set email alerts
|

Truss optimization on shape and sizing with frequency constraints based on genetic algorithm

Abstract: Truss optimization on shape and sizing with frequency constraints are highly nonlinear dynamic optimization problems. Coupling of two different types of design variables, nodal coordinates and cross-sectional areas, often lead to divergence while multiple frequency constraints often cause difficult dynamic sensitivity analysis. So optimal criteria method and mathematical programming, which need complex dynamic sensitivity and are easily trapped into the local optima, are difficult to solve the problems. To sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(46 citation statements)
references
References 12 publications
(21 reference statements)
0
43
0
3
Order By: Relevance
“…The sensitivity analyses are carried out on the CBBO From Tab. 2, in Case 1 , it can be concluded that CBBO gives lightest design as compared to the results obtained by Grandhi and Venkayya [2], Sedaghati and et al [3], Wang et al [5] and Lingyun et al [10], but slightly heavier design than DPSO [12] method. Also it is clear that the values of mean weight and standard deviation for CBBO are relatively less than other methods.…”
Section: Design Examplesmentioning
confidence: 53%
See 3 more Smart Citations
“…The sensitivity analyses are carried out on the CBBO From Tab. 2, in Case 1 , it can be concluded that CBBO gives lightest design as compared to the results obtained by Grandhi and Venkayya [2], Sedaghati and et al [3], Wang et al [5] and Lingyun et al [10], but slightly heavier design than DPSO [12] method. Also it is clear that the values of mean weight and standard deviation for CBBO are relatively less than other methods.…”
Section: Design Examplesmentioning
confidence: 53%
“…5, the results obtained by the CBBO and BBO are compared with those reported in the literature like NHGA [10], PSO [11], CSS, enhanced CSS [29] and DPSO [12]. From this table, it can be observed that CBBO significantly outperforms other methods in terms of the values of best, mean and standard deviation, which shows its stability in reaching the optimal weight of the structure during 20 independent runs.…”
Section: Example 2 a Simply Supported 37-bar Planar Trussmentioning
confidence: 85%
See 2 more Smart Citations
“…Lingyun et al [240] presentaron un Algoritmo Genético sometido a restricciones de frecuencia, aplicándolo a la estructura de diez barras, un puente estudiado previamente por Wang y Arora [406] y una cúpula de 52 barras.…”
Section: Canyurt Y Hajela [55] Utilizaron Un Autómata Celular Basado unclassified